The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/nin.12372
|View full text |Cite
|
Sign up to set email alerts
|

Rituals, ghosts and glorified babysitters: A narrative analysis of stories nurses shared about working the night shift

Abstract: Working the night shift can be fraught and experienced as demanding and, yet, is often dismissed as babysitting. Few researchers have explored the social and cultural meanings of night nursing, including storytelling rituals. In 2019, a narrative study was undertaken. The aim was to explore the stories recalled by nurses about working night shifts. Thirteen Australian nurses participated. Data were gathered using the Biographical Narrative Interview Method, and narrative analysis produced forty stories and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 19 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…A total of 33 studies (34 reports, as one study was reported across two articles) were reviewed for methodological quality and were of moderate to high quality: Four articles38-41 met all 10 of the critical appraisal criteria, six articles42-47 met nine of the criteria, nine articles48-56 met eight of the criteria, 13 articles57-68,70 met seven of the criteria, one article71 met six of the criteria, and one article69 met five of the criteria. All studies rated positively for questions related to congruity between research methodology and research question (Q2), research methodology and methods (Q3), research methodology and representation of the analysis of data (Q4), and voices represented (Q8).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 33 studies (34 reports, as one study was reported across two articles) were reviewed for methodological quality and were of moderate to high quality: Four articles38-41 met all 10 of the critical appraisal criteria, six articles42-47 met nine of the criteria, nine articles48-56 met eight of the criteria, 13 articles57-68,70 met seven of the criteria, one article71 met six of the criteria, and one article69 met five of the criteria. All studies rated positively for questions related to congruity between research methodology and research question (Q2), research methodology and methods (Q3), research methodology and representation of the analysis of data (Q4), and voices represented (Q8).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that younger and less experienced MHN are not as resilient as more experienced nurses (Delgado et al, 2020; Foster et al, 2020; Zheng et al, 2017) and less experienced MHN would gain from specific support for their resilience and practice. Given the benefits of storytelling in helping others to develop their own strengths (McAllister et al, 2020), we recommend narrative techniques are used to support both novice and experienced MHNs to reflect on their practice. Narrative‐informed clinical supervision is also recommended, where narratives of practice situations are co‐created and explored between supervisee and supervisor for the purpose of building self‐awareness and improving practice (Stevenson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to explore mental health nurses' stories of resilience in their practice. Nursing is a storied profession and stories can be a powerful tool for sharing experience, connecting nurses, building empathy and a sense of community, and motivating others to action and change (McAllister et al, 2020). As stories are central to human meaning-making, they are important for understanding human experience, and research itself can be seen as a storytelling act (Lewis, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Few reported a second job at baseline, and we do not consider it an important source of bias. Night work is associated, among others, with lower staffing 36 and more injuries, 37 and it cannot be ruled out that such factors may influence the relationship between night work and sleep medication use. Due to lack of information of these factors, we were however not able to adjust for these in the analyses.…”
Section: Discussionmentioning
confidence: 99%